Continuum of Care: Positioning of the Virtual Hospital - van der Lande, Anne Catherine M. H.; Treskes, Roderick W.; Beeres, Saskia L. M. A.; Schalij, Martin J. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Patients with multiple chronic diseases suffer from reduced life expectancy. Care for these patients is often divided over multiple healthcare professionals. eHealth might help to integrate care for these patients and create a continuum. It is the primary purpose of this paper to describe an intervention that integrates first, second and third line care in patients with multiple chronic conditions using remote monitoring, remote therapy and data automatization, all integrated in a virtual care center (VCC). Methods: Patients diagnosed with three or more chronic conditions are included and given smartphone compatible devices for remote monitoring and a tablet for video consultations. Patients will be followed-up by the VCC, consisting of nurses who will coordinate care, supervised by general practitioners and medical specialists. Data is reviewed on a daily basis and patients are contacted on a weekly basis. Review of data is automated by computer algorithms. Patients are contacted in case of outcome abnormalities in the data. Patients can contact the VCC at any time. Follow-up of the study is one year. Results: The primary outcome of this study is the median number of nights admitted to the hospital per patient compared to the hospitalization data twelve months before enrolment. Secondary outcomes include all-cause mortality, event free survival, quality of life and satisfaction with technology and care. Conclusion: This study presents the concept of a VCC that integrates first, second and third line care into a virtual ward using remote monitoring and video consultation.